Didactics courses in Special Education: their changes throughout the 50 years of the career at the University of Costa Rica - Carpio Brenes, María de los Angeles (2025)
The evolution of Special Education (EE) in Costa Rica has been a notable process, characterized by the transition from a medical point of view in the mid-20th century to an inclusive perspective today. It emerges as the main reflection that going Special Education in Costa Rica has evolved significantly a rehabilitative approach in 1940 where the person with a disability was attended to by a “teacher specializing in…” to a more social perspective today, where now “educational support teacher” collaborates in the elimination of barriers to participation and learning of student diversity. In this epistemological change and teaching actions, the Special Education program at the UCR has played a relevant role as a transformative agent, as evidenced in the modifications to the study plans and course programs in its 50 years of existence. As a conclusion, the changes in the teaching programs of reading, writing and mathematics respond to the historical evolution of the discipline and the paradigm of the moment, because the conception of disability of a certain era marks the role of the special educator in that specific educational context.